The isolation and purification of pigments from fruits rinds of Musa sp. using thin layer and column chromatography. - Samonte, Ma. Donna A. (1984.)
Banana fruit rinds are major waste products of the banana industry. This study aimed to explore the possibility of converting this waste material into a valuable product through the isolation and purification of the pigments using thin layer and column chromatography. Lacatan (sample A), tundal (sample B), morado (sample C), and balangon (sample D) were the four species of banana used., Isolation of the pigments using the solvent extraction method revealed a percent yield of 17.5, 15.94, 16.34, and 15.83 for samples A, B, C, and D, respectively. Yellow, green and reddish spots were detected in the TLC using three different solvent systems: Pet. ether-chloroform-carbon tetrachloride-glacial acetic solution - - - 1:1:1:1 (solvent system) pet. ether-chloroform-carbon tetrachchloride-glacial acetic and acid solution - - - 1:1:2:1 (solvent system II), and, pet. ether-ethanol-carbon tetrachloride-glacial acetic acid solution- - - 1:1:1:1 (solvent system III). In the Column chromatography, yellow, green and orange pigments were collected. Based on the over-all result, the study was said to be successful. However, further study on the nature of the samples and the identification and characterization of the isolated pigments are recommended.
Thesis (Undergraduate, Bachelor of Science, Natural Sciences) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Fruits Rinds